2002
DOI: 10.1086/339472
|View full text |Cite
|
Sign up to set email alerts
|

Runaway Merging of Black Holes: Analytical Constraint on the Timescale

Abstract: Following the discovery of a black hole (BH) with a mass of 10^3-10^6 M(sun) in a starburst galaxy M82, we study formation of such a BH via successive merging of stellar-mass BHs within a star cluster. The merging has a runaway characteristic. This is because massive BHs sink into the cluster core and have a high number density, and because the merging probability is higher for more massive BHs. We use the Smoluchowski equation to study analytically the evolution of the BH mass distribution. Under favorable co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 26 publications
5
115
0
1
Order By: Relevance
“…For a generic PBH mass spectrum, the number of collisions per volume and time is given bȳ To perform our estimate, we assume a very narrow distribution of black hole masses corresponding to a relatively large value of δ in the model (4.1); in this case, we can assume a single value for the mass in the cross section (4.10), see [48,79],…”
Section: Gw From Merging Pbhsmentioning
confidence: 99%
“…For a generic PBH mass spectrum, the number of collisions per volume and time is given bȳ To perform our estimate, we assume a very narrow distribution of black hole masses corresponding to a relatively large value of δ in the model (4.1); in this case, we can assume a single value for the mass in the cross section (4.10), see [48,79],…”
Section: Gw From Merging Pbhsmentioning
confidence: 99%
“…The PBH pair becomes gravitationally bound if the GW emission exceeds the initial kinetic energy. The cross section for this process is [19,20] where M pbh is the PBH mass, and M 30 the PBH mass in units of 30 M , R s = 2GM pbh /c 2 is its Schwarzschild radius, v pbh is the relative velocity of two PBHs, and v pbh−200 is this velocity in units of 200 km sec −1 . We begin with a rough but simple and illustrative estimate of the rate per unit volume of such mergers.…”
mentioning
confidence: 99%
“…The PBH pair becomes gravitationally bound if the GW emission exceeds the initial kinetic energy. The cross section for this process is [19,20] …”
mentioning
confidence: 99%
“…Previous studies have suggested that interactions in this dense cluster can produce many BH-BH mergers, whether through evaporated binaries [4] or through runaway BH-BH mergers in the dense cluster itself [30,31,32]. However, these studies have faced significant objections to their details, because each has omitted some feature which could significantly inhibit the channel suggested.…”
mentioning
confidence: 99%